Synchronization of Time Delayed Fractional Order Chaotic Financial System - Weiwei Zhang; Jinde Cao; Ahmed Alsaedi; Fuad Eid S. Alsaadi (Discrete Dynamics in Nature and Society)
The research on a time delayed fractional order financial chaotic system is a hot issue. In this paper, synchronization of time delayed fractional order financial chaotic system is studied. Based on comparison principle of linear fractional equation with delay, by using a fractional order inequality, a sufficient condition is obtained to guarantee the synchronization of master-slave systems. An example is exploited to show the feasibility of the theoretical results.